Effect of southern climate modes and variations in river discharge on lake surface area in Patagonia. Issue 3 (3rd July 2018) - Scordo, Facundo; Perillo, Gerardo M. E.; Cintia Piccolo, M.
ABSTRACT: Multiple regressions, wavelet spectra, and Fourier spectra were employed to analyze fluctuations in the surface areas of 2 Patagonian lakes during 1998–2015 and relate these to fluctuations in precipitation, evaporation, river discharge, and 2 southern climate modes, the Antarctic Oscillation (AAO) and El Niño Southern Oscillation, expressed in terms of the Southern Oscillation Index (SOI). Multiple regression analysis suggested that discharge was the primary driver of interannual lake area variations. Cross-spectrum analysis demonstrated a maximum significant correlation between river discharge and both AAO and SOI indices at annual and interannual timescales (2–3 yr). During 1998–2015, the annual discharge signal was related to both the AAO annual and every 2 year signals. When a strong La Niña (positive SOI) event occurred, however, river discharge was significantly reduced, resulting in a decrease in lake surface area.